Curtailing examination fraud for improved quality assurance in the African examination system (2011)
The recurrent incidence of examination malpractices on the African continent particulary in Nigeria calls for drastic measures to arrest the situation. The study investigates the nature, causes, methods and effects of examination malpractices and sought out how the quality of regional examinating systems can be assured therby. The study was a descriptive survey design using ex-post facto research type to collect data. The sample was made up of 80 teachers and 400 students, respectively. Data were analysed using percentages, graphs and charts. The findings were that examination malpractice occurs at all levels of the system in diverse ways: leakage of question papers in the process of setting, printing, packaging, storing, and distribution. Others included: impersonation, undue favoritism by invigilators of students, bribing or influencing examination staff, councils' allotment of choice examination centres termed "special" "miracle" centres and inflation or reduction of canditates' original scores by those who mark or grade the scripts. It was also discovered that students carry out examination malpractices by various means: desktop publishing and laptop publishing. Some of the causes of this examinational menace included greed, corruption, dishonesty, indolence and lethargy, students' poor study habits and compromise. The effects and the way outproblem were discussed. Recommendations included stakeholders must corporately fight against this vice. Communities, government, corporate bodies, and examinating bodies should come together in the region to educate stakeholders, from time to time, on the appropriate teaching and learning techniques as well as conduct researches that will improve classroom interaction and preparation for the examinations.